2001
DOI: 10.1093/emboj/20.6.1271
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of TRAF6-mediated signaling pathways clarifies its role in osteoclastogenesis

Abstract: N.Kobayashi and Y.Kadono contributed equally to this workSignals emanating from the receptor for interleukin-1 (IL-1), lipopolysaccharide (LPS) or osteoclast differentiation factor/receptor activator of NFkB ligand (ODF/RANKL) stimulate transcription factors AP-1 through mitogen-activated protein kinase (MAPK) activation and NFkB through IkB kinase (IKK) activation. These kinases are thought to be activated by tumor necrosis factor receptor-associated factor 6 (TRAF6). However, molecular mechanisms by which TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
347
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 434 publications
(360 citation statements)
references
References 44 publications
11
347
1
1
Order By: Relevance
“…It has become clear that RANK transduces key signals by directly interacting with TRAF6 [24,25]. In addition, it has been reported that PLCγ2 binds to Gab2 in response to RANKL, mediates Gab2 recruitment to RANK, and is required for osteoclast formation [10,20].…”
Section: Discussionmentioning
confidence: 99%
“…It has become clear that RANK transduces key signals by directly interacting with TRAF6 [24,25]. In addition, it has been reported that PLCγ2 binds to Gab2 in response to RANKL, mediates Gab2 recruitment to RANK, and is required for osteoclast formation [10,20].…”
Section: Discussionmentioning
confidence: 99%
“…51 Functional domains of TRAF6 involved in MAPK activation have been characterized. 53 Among the various domains investigated, the RING finger and the first zinc finger domains are required for activation of TAK1 and downstream p38 and JNK MAPK 53 ( Figure 3). Moreover, TRAF6 has also been demonstrated to activate p38 and JNK MAPK during osteoclast differentiation by favoring ROS production through increased NAPDH oxidase activity 54 (Figure 3).…”
Section: The P38 Mapk Signaling Pathway In Osteoclastsmentioning
confidence: 99%
“…COS7 cells were cultured in DMEM supplemented with 10% FCS and antibiotics (complete DMEM). Wild-type (WT) murine embryonic fibroblast (MEF), TRAF6-deficient (TRAF6 Ϫ/Ϫ ) MEF (20), and Plat-E cells (21) were established and maintained as described elsewhere.…”
Section: Cell Culturementioning
confidence: 99%
“…It has been reported that TRAF6 is involved in the signaling pathways of IL-1-and IL-17-induced NF-B activation (20,25,26). To determine whether TRAF6 is involved in IL-25R-mediated signaling, we investigated the effect of a DN TRAF6 on IL-25R-mediated NF-B activation.…”
Section: Traf6 Is Crucial For Il-25r-mediated Nf-b Activationmentioning
confidence: 99%